I know how I want to be assessed: Empowering undergraduate students through self-and peer-assessment strategies - Sathasivam, Renuka V. (2017)
Traditionally, assessment of undergraduate students' learning outcomes is pre-determined by lecturers and more often it remains a covert affair. Since undergraduate students remain at the peripheral of the assessment process, many of them do not gain a sense of what is important or valued in their field of study. Formative assessment advocators often stress the importance of students' involvement in the assessment process especially through self- and peer-assessment strategies. These strategies enable students to take ownership and responsibility for their learning and eventually become autonomous learners, a pivotal skill for the twenty-first century. The aim of this study was to investigate how students engage in the process of self- and peer-assessment; firstly, in the creation of a scoring rubric and secondly, to use the rubric to assess their peers (i.e. providing constructive feedback). Since the concept of self- and peer-assessment was relatively new, initially steps were taken to introduce these concepts. The participants of this study were a cohort of pre-service science teachers. The pre-service teachers were in their final year at the university before moving on to do their practical training at local schools. Qualitative data collection techniques such as classroom observations, interviews and document analysis were used as sources of data. Initial findings revealed that even though the pre-service teachers were clear of what they would like to be assessed on, they found it a challenge to do peer-assessment especially when they had to provide feedback on the peers' work. The conclusion can be drawn that these undergraduate students might be unable to verbalize their thoughts coherently to help their peers with their work especially on how to critically improve their work. Following an in-depth analysis of preliminary research results, some recommendations of how to conduct self- and peer-assessment will be presented.